Manulak Sere Tradition in Traditional Marriage in Tanjung Botung Village Padang Lawas Regency According to Compilation of Islamic Law (KHI) Perspective - Nasution, Mahdi; Pasaribu, Ilham Syah (Universitas Islam Sultan Agung, 2023)
Tradition is a set of values, beliefs, beliefs and symbols that guide human behavior in realizing ways of life. Marriage is one of the religious orders for someone who is able to carry it out immediately. The Mandailing community is one of the North Sumatra groups that maintains traditional social customs today including the Manulak Sere tradition. Researchers want to examine how the Compilation of Islamic Law actually views the community tradition regarding the Manulak Sere tradition. What is the reason why the people of Padang Lawas, especially in Tanjung Botung Village, carry out the Manulak Sere tradition even though in Islamic Law it is not recommended. Furthermore, how is the KHI review of the Manulak Sere tradition in marriage. In the perspective of the Compilation of Islamic Law (KHI), the Manulak Sere tradition does not contradict the nash in the Qur'an and Hadith. However, the Manulak Sere tradition carried out in the Padang Lawas community, especially Tanjung Botung Village, is the Compilation of Islamic Law (KHI) Shahih. This tradition has no conflict with Islamic law. The people of Padang Lawas, especially Tanjung Botung Village, carry out marriage ceremonies in accordance with Islamic law. However, they also cannot abandon customary law, which their ancestors have practiced since ancient times. So it is clear that: Islamic law and customary law both get their respective portions. The implementation of this tradition is not considered by the community as a valid requirement for marriage according to Islam.